Protocol: Waiting time and ways of accessing specialized health services in public hospitals in Ecuador - Marcelo Armijos Briones; Sammy Figueroa Intriago; Antonio Lanata-Flores; Pablo Benitez Sellán; Oscar Marcillo Toala; Patricia Estefanía Ayala Aguirre (PLoS ONE, 2025)
This study aims to determine the waiting time and the forms of access to specialized health services in public hospitals in Ecuador. A representative sample of 32 hospitals under the Ministry of Public Health was considered, with 26 selected by accessibility convenience. Data will be collected using a structured questionnaire. Patients will be asked about the number of days they waited for their medical appointments and the method used to schedule their appointments. The study distinguishes between standardized access, based on Ecuador’s formal referral and counter-referral system, and non-standardized access methods, such as personal connections or hospital staff involvement. The data of this protocol are registered and publicly accessible at: https://dx.doi.org/10.17504/protocols.io.261ge5z7wg47/v1 . We expect to identify a correlation between waiting times and the type of access to specialized medical services, with non-standardized access potentially leading to shorter waiting times. This research may highlight disparities in the system and suggest areas for improvement in equity and efficiency within the healthcare referral process. To do so, a structured survey will be used. Since a construct is not needed to determine the waiting time or the forms of access, it was not necessary to validate the instrument. However, we did validate the understanding of the questions and the response options in several places in the country. According to the results of the validation of the instrument, pollsters will be instructed to inform users about the meaning of the question on ethnic identification, which was difficult to understand in the country’s coastal areas.